2019
DOI: 10.3389/fphys.2019.01362
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a New Specific Parkour Test: Physiological and Performance Responses

Abstract: Main aim of this study was examining validity and reliability of using a new specific Parkour repeated sprint ability test (SPRSA) for assessing repeated sprint ability while facing obstacles and establishing between-day reliability and sensitivity of SPRSA related to its physiological and performance responses. Thirteen high-level traceurs (three females) performed in random order and twice eight tests for assessing a total of 23 variables: SPRSA (a typical maximal-speed shuttle run interspersed with four Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…1) and thus it is a standard test that represents a good starting point to compare traceurs' to other athletes' performances. This comparison has shown that, despite a less controlled and structured training, traceurs could achieve similar or even better performances than other athletes (Table 2) [38,57,62,66,67]. In fact, the average performance of traceurs in SLJ is 248.0 ± 28.1 cm (mean values extrapolated from the studies presented in Table 2), which is comparable or greater than the performance of other high-level athletes (gymnastics SLJ = 251.1 ± 13.5 cm ; various sports SLJ = 223.8 ± 14.9 cm), notwithstanding that the variability is large enough that one should make sure not to draw any definitive conclusion (Table 2).…”
Section: Iii2 Performance Assessmentmentioning
confidence: 99%
“…1) and thus it is a standard test that represents a good starting point to compare traceurs' to other athletes' performances. This comparison has shown that, despite a less controlled and structured training, traceurs could achieve similar or even better performances than other athletes (Table 2) [38,57,62,66,67]. In fact, the average performance of traceurs in SLJ is 248.0 ± 28.1 cm (mean values extrapolated from the studies presented in Table 2), which is comparable or greater than the performance of other high-level athletes (gymnastics SLJ = 251.1 ± 13.5 cm ; various sports SLJ = 223.8 ± 14.9 cm), notwithstanding that the variability is large enough that one should make sure not to draw any definitive conclusion (Table 2).…”
Section: Iii2 Performance Assessmentmentioning
confidence: 99%
“…Rather than developing maximum power as in track and field disciplines, parkour involves producing the right amount of power in order to reach accurately the targeted distance [70]. Since tests from other sports are not adapted to fully evaluate the multiplicity of parkour skills, specific tests are starting to be developed [71][72][73].…”
Section: Ii2 Performance Assessment In Parkourmentioning
confidence: 99%
“…Plank test was modified according to Padulo et al [32]. This test aimed at holding an elevated position for as long as possible.…”
Section: Plankmentioning
confidence: 99%